2017
DOI: 10.1007/s00125-017-4385-1
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic crosstalk between fatty pancreas and fatty liver: effects on local inflammation and insulin secretion

Abstract: Aims/hypothesis Obesity-linked ectopic fat accumulation is associated with the development of type 2 diabetes. Whether pancreatic and liver steatosis impairs insulin secretion is controversial. We examined the crosstalk of human pancreatic fat cells with islets and the role of diabetogenic factors, i.e. palmitate and fetuin-A, a hepatokine released from fatty liver. Methods Human pancreatic resections were immunohistochemically stained for insulin, glucagon, somatostatin and the macrophage/monocyte marker CD68… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
118
0
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 122 publications
(128 citation statements)
references
References 54 publications
5
118
0
5
Order By: Relevance
“…Mouse islets cultured in media with elevated fatty acid levels resulted in increased intracellular triglyceride storage, as evidenced by Oil Red O (ORO)‐positive staining, coincident with morphological changes in the islets and reduced glucose‐stimulated insulin secretion (GSIS) performance . Moreover, a study of isolated human islets cocultured with pancreatic adipocytes showed that adipocyte‐secreted cytokines (interleukins 6 and 8 and MCP‐1) impair GSIS through inflammation of the islet milieu …”
Section: Introductionmentioning
confidence: 99%
“…Mouse islets cultured in media with elevated fatty acid levels resulted in increased intracellular triglyceride storage, as evidenced by Oil Red O (ORO)‐positive staining, coincident with morphological changes in the islets and reduced glucose‐stimulated insulin secretion (GSIS) performance . Moreover, a study of isolated human islets cocultured with pancreatic adipocytes showed that adipocyte‐secreted cytokines (interleukins 6 and 8 and MCP‐1) impair GSIS through inflammation of the islet milieu …”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have indicated a robust cross-talk between fatty pancreas and fatty liver affecting the local inflammation and insulin secretion by the islets cells. In these studies, differentiated adipocytes were detected in the vicinity of pancreatic islet cells [19,79]. Expression levels of cytokines such as IL6 and CXCL8 were elevated by fetuin-A and free fatty acids such as palmitate in a TLR4-dependent manner [19,79,89].…”
Section: Action Of Fetuin-a On β-Islets Cells Of the Pancreasmentioning
confidence: 99%
“…In these studies, differentiated adipocytes were detected in the vicinity of pancreatic islet cells [19,79]. Expression levels of cytokines such as IL6 and CXCL8 were elevated by fetuin-A and free fatty acids such as palmitate in a TLR4-dependent manner [19,79,89]. Interestingly, it has been demonstrated that free fatty acids such as palmitate do not bind directly to TLR4 but rather via fetuin-A [78].…”
Section: Action Of Fetuin-a On β-Islets Cells Of the Pancreasmentioning
confidence: 99%
See 2 more Smart Citations